2021
DOI: 10.1038/s41598-021-83928-0
|View full text |Cite
|
Sign up to set email alerts
|

Pre-procedural proton pump inhibition is associated with fewer peri-oesophageal lesions after cryoballoon pulmonary vein isolation

Abstract: Pulmonary vein isolation (PVI) using cryoenergy is safe and efficient for treatment of atrial fibrillation (AF). Pre-existing upper gastrointestinal (GI) pathologies have been shown to increase the risk for AF. Therefore, this study aimed at assessing incidental pathologies of the upper GI tract in patients scheduled for PVI and to analyse the impact of patients’ characteristics on PVI safety outcome. In 71 AF patients, who participated in the MADE-PVI trial, oesophagogastroduodenoscopy and endosonography were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…| 1173 local ischemia and necrosis of the esophageal wall 14 and potentially fistula formation. 15 The results of our study confirm the lack of predictive value of LET alone, and the suggested temperature limits are still controversial. 11,12,16,17 LET is simply a poor surrogate of tissue temperature, the distance of the closest electrode may impede detection of relevant tissue temperature increases, 12,[18][19][20] and LET maximum values ignore the impact of temporal and spatial components.…”
Section: Notesupporting
confidence: 66%
See 1 more Smart Citation
“…| 1173 local ischemia and necrosis of the esophageal wall 14 and potentially fistula formation. 15 The results of our study confirm the lack of predictive value of LET alone, and the suggested temperature limits are still controversial. 11,12,16,17 LET is simply a poor surrogate of tissue temperature, the distance of the closest electrode may impede detection of relevant tissue temperature increases, 12,[18][19][20] and LET maximum values ignore the impact of temporal and spatial components.…”
Section: Notesupporting
confidence: 66%
“…Periesophageal edema detected by EUS and gastric motility disorders (food retention) accounted for a relevant proportion of esophageal injury in this cohort, and endoscopy therefore may underestimate the true incidence of ablation‐induced injury. Although the clinical relevance is still debated, edema might be associated with occlusion of periesophageal arteries, leading to local ischemia and necrosis of the esophageal wall 14 and potentially fistula formation 15 …”
Section: Discussionmentioning
confidence: 99%
“…The evidence for some effect in reducing esophageal thermal lesions was suggested by a sub-study of the MADE-PVI trial. 56 This study found that pre-procedural use of proton pump inhibitors reduced esophageal/mediastinal lesions as assessed by endoscopic ultrasound as well as pre and post upper GI endoscopy.…”
Section: Proton Pump Inhibitors (Ppi)mentioning
confidence: 66%
“…On the one hand, edema might be an unspecific response of the surrounding tissue due to the very limited thermal effects of PFA, 13 and mechanisms besides its thermal profile (e.g., induction of an inflammatory cascade) 28 might also play a role. On the other hand, it may be due to pre‐existing inflammation of esophageal tissue (i.e., chronic esophagitis or reflux) and not due to the ablation itself 17,18,29 …”
Section: Discussionmentioning
confidence: 99%